Kamisama kiss. Vol. 10 - Suzuki, Julietta (Viz Media, 2012)
Nanami Momozono is left homeless when her father skips town on a gambling debt. When she saves a man from a dog, she is offered a home, but the place is a shrine where Nanami is to become a local deity.